Analisis Pemanfaatan Minyak Jelantah Menjadi Gliserol Dengan Metode Hidrolisis - Monik Kasman; Hadrah Hadrah; Suraya Suraya; Brian Andika (Universitas Batanghari Jambi, 2023)
This study aims to determine the effectiveness of the hydrolysis method in the manufacture of glycerol from used waste cooking oil. This experiment was carried out by the Hydrolysis method. The hydrolysis process is carried out by varying the ratio of reactants between the amount of used waste cooking oil & water, namely (20:180; 40:160; 100:100; 140:60 ml). In addition, HCl & KOH solutions are used as catalysts in the hydrolysis process.From the results of the study, the maximum glycerol yield value was 0.79% in the ratio of reactants (20ml used waste cooking oil: 180ml water) with a reaction time of 1 hour, 3% HCl catalyst concentration and a temperature of 100°C.